2017
DOI: 10.1177/0081246317743185
|View full text |Cite
|
Sign up to set email alerts
|

The factor structure of the Normative Beliefs about Aggression Scale as used with a sample of adolescents in low socio-economic areas of South Africa

Abstract: The issue of adolescent aggression and violence has received significant attention in the literature. Normative beliefs about the acceptability of aggressive behaviour have been identified as central in influencing aggression. The Normative Beliefs about Aggression Scale was developed to identify cognitive beliefs about the acceptability of aggressive behaviour. The scale has been extensively used in research on child and adolescent aggression and has consistently demonstrated that normative beliefs account fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 45 publications
4
1
0
Order By: Relevance
“…Unfortunately, none of these models fit the data well. We verified the other four models proposed by Padmanabhanunni (2019), who also tested the bi-factor model with the factor for general approval of aggression ("Alt 1"), the gender-specific hierarchical model ("Alt 2"), the approval of retaliation hierarchical model ("Alt 3"), and the one-factor model ("Alt 4"). Even these models did not fit the data well and had serious problems with multi-collinearity of latent variables, and some did not converge.…”
Section: Normative Beliefs About Aggression Scalesupporting
confidence: 66%
“…Unfortunately, none of these models fit the data well. We verified the other four models proposed by Padmanabhanunni (2019), who also tested the bi-factor model with the factor for general approval of aggression ("Alt 1"), the gender-specific hierarchical model ("Alt 2"), the approval of retaliation hierarchical model ("Alt 3"), and the one-factor model ("Alt 4"). Even these models did not fit the data well and had serious problems with multi-collinearity of latent variables, and some did not converge.…”
Section: Normative Beliefs About Aggression Scalesupporting
confidence: 66%
“…However, the other cultural factors characterizing Vietnam (power inequality, the socio-economical development, and the promotion of harsh parenting practices) could have resulted in a level of ambivalence to some aspects of the normative beliefs towards aggression, due to which we could not fully replicate the Western factor structure. Such an interpretation would be in line with previous research that indicated the influences of cultural characteristics on the development of normative beliefs supporting aggression in non-Western societies (Amjad & Wood, 2009;Lim & Ang, 2009;Padmanabhanunni, 2019).…”
Section: Discussionsupporting
confidence: 88%
“…The internal consistency of the Bangla NOBAGS has been quite alike the NOBAGS translated in other languages (Table 8). The high-reliability estimates for the total scale are consistent with the original scale (12) and other adaptation work (37) . (37) South Africa 229 1-20 Cronbach's α .84…”
Section: Scale Itemssupporting
confidence: 84%
“…The high-reliability estimates for the total scale are consistent with the original scale (12) and other adaptation work (37) . (37) South Africa 229 1-20 Cronbach's α .84…”
Section: Scale Itemssupporting
confidence: 84%